False realities: Hoaxes on the Palestine–Israel conflict in Indonesia’s digital media - Abiano Al Affan (Priviet Social Sciences Journal, 2026)
Hoaxes are among the major digital challenges with the potential to erode national values. The significant impact of hoax content has drawn the attention of many parties to further explore this issue. One of the most discussed topics in recent times is the Palestine–Israel conflict. Studies on hoax content related to the conflict on Indonesian social media remain limited. This study aims to examine which platforms are most frequently used in disseminating hoax content, identify the dominant themes, and analyze how hoax content constructs false realities based on McCornack’s (1992) Information Manipulation Theory (IMT). Content analysis and semiotic analysis were employed as the research methods. Data were obtained from hoax news reports published on the official government website (www.komdigi.go.id). The findings reveal that Facebook is the platform with the highest prevalence of hoax content, followed by TikTok, Instagram, X, WhatsApp, and YouTube. The military theme dominated, followed by humanitarian, political, religious, and other themes. The construction of hoax content aligns with IMT, demonstrating violations of quality, quantity, manner, and relevance. These findings contribute to a deeper understanding of how digital hoaxes operate in conflict-related contexts and provide insights for digital media practitioners in designing effective hoax mitigation strategies.